State of recreational and health-improving forests in Kharkiv Region - Musienko, S. I.; Bondarenko, V. V.; Tarnopilska, O. M.; Rumіantsev, M. Н.; Kobets, O. V.; Luk’yanets, V. A. (Forestry and Forest Melioration, 2020)
Introduction Due to its geographical location, climatic features and historical anthropogenic transformation of forests, Kharkiv Region belongs to the sparsely forested regions in Ukraine. The forest cover in the region makes 12.1% and does not reach its optimal level (17–20%), at which forests maximize their positive impact on climate, soils, and water resources. Forests of the region are classified as having high environmental, protective, social, recreational and health values. Most of them are identified as recreational and health-improving forests. Therefore, the study of the current state of recreational and health-improving forests will provide a scientific basis for ways to preserve, protect, rationally use and effectively reproduce them as well as to increase their resilience and enhance their useful functions. Materials and Methods The state of Ukrainian recreational and health-improving forests was analysed according to the Ukrderzhlisproekt Production Association database as of 01.01.2011. The forests are in a permanent use of state forest enterprises subordinated to the State Forest Resources Agency of Ukraine. Results The analysis of the subcompartment database shows that recreational and health-improving forests in Kharkiv Region cover an area of about 139 thousand hectares or 49.1% of the total forest area. At that, forests of green belts around settlements with the area proportion of 90% predominate. The recreational and health-improving forests in Kharkiv Region are mostly deciduous stands (73.5%); in particular, they are oak stands growing in rich types of forest site conditions, namely fresh fertile site type. Coniferous stands, mainly pine ones, occupy 26.5% of the total area and grow typically in fresh fairly infertile sites. Low-yield maturing and mature coppice oak stands dominate in the recreational forests of the region. The efficiency of their recreational functions is gradually declining. There is a steady trend towards aging of the oak stands of vegetative origin. These forests require proper forestry measures which will ensure growing highly productive, sustainable, long-living, and highly ornamental stands, so that the latter will be able to effectively perform their essential environmental functions. The issues concerning the species composition expanding in recreational and health-improving forests to enhance their sanitary and aesthetic benefits are relevant. Conclusions Considering that specific peculiarities of forest management for the currently assigned subcategories of recreational and health-improving forests have not been defined yet, a further study for forest management in these forests is recommended to improve the method for relevant subcategory identification. 4 Tables, 17 Refs. Key words: forest categories, forest site condition types, forest-forming species.